2015
DOI: 10.1016/j.pharep.2015.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Vascular diseases investigated ex vivo by using Raman, FT-IR and complementary methods

Abstract: This work shows the application of vibrational spectroscopy supported by other complementary techniques in analysis of tissues altered by vascular diseases, in particular atherosclerosis. The analysis of atherosclerotic plaque components, as well as label-free imaging of vessels and identification of biochemical markers of endothelial dysfunction are reported. Additionally, the potential of vibrational spectroscopy imaging in following the disease progression (including calcification) and pathological changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…Full field of view (fFOV) MiROM images are included of Spectral peaks were assigned to vibrational modes, based on literature review of Raman and FTIR measurements of atherosclerotic tissues [14] , [19] , [20] , see Table 1 . The signal at 2850 cm −1 originates mainly from the symmetric stretching of CH 2 , which, though not exclusive of lipids, is stronger for lipids than for other biomolecules [24] . Wavelengths relating to the same class of molecules (such as 1171 cm −1 and 1735 cm −1 for CE, Fig.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Full field of view (fFOV) MiROM images are included of Spectral peaks were assigned to vibrational modes, based on literature review of Raman and FTIR measurements of atherosclerotic tissues [14] , [19] , [20] , see Table 1 . The signal at 2850 cm −1 originates mainly from the symmetric stretching of CH 2 , which, though not exclusive of lipids, is stronger for lipids than for other biomolecules [24] . Wavelengths relating to the same class of molecules (such as 1171 cm −1 and 1735 cm −1 for CE, Fig.…”
Section: Resultsmentioning
confidence: 95%
“…The technique may prove similarly insightful in neurodegenerative diseases or cancer, where deposition of aberrant tissue leads to disease and even death. Mid-IR spectroscopic imaging studies of tissue composition in atherosclerosis have been reported previously [12] , [13] , [14] , [24] , [28] , [29] , [30] . Stimulated Raman Scattering imaged structures that could be identified as CC [31] .…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, monitoring pathological alterations caused by Aeromonas infection and determining disease biomarkers can provide valuable insight into the mechanisms of pathogenicity. FT-IR spectroscopy has been increasingly applied as a versatile diagnostic tool in neurodegenerative diseases [ 61 ], cardiovascular disorders [ 62 ], and cancers [ 63 ] by analyzing biofluids, tissues, or cells, which is confirmed in many biological and biomedical studies [ 64 ]. Its ability to detect changes in the morphology and chemical composition of intact cells contributed to its utility in discrimination between diseased and normal biological samples [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…27 Raman spectroscopy also revealed that the tyrosine (Tyr) to phenylalanine (Phe) ratio was changed in ED in atherosclerosis. 28 Tetrahydrobiopterin (BH4) is a key regulator of endothelial nitric oxide synthase (eNOS), and therefore, limitation of BH4 availability triggers ED and is reflected by changes in the synthesis of Tyr from Phe that depend on the presence of BH4 as a cofactor of phenylalanine hydroxylase (PAH). 29 Accordingly, alterations in the Tyr to Phe ratio may indicate ED.…”
Section: Raman Spectroscopic Markers Of Endothelial Dysfunction Studi...mentioning
confidence: 99%